Tobacco smoking and the risk of gallbladder disease - Aune, Dagfinn; Vatten, Lars J.; Boffetta, Paolo (European journal of epidemiology, 2016)
Tobacco smoking has been inconsistently associated with gallbladder disease risk. To clarify the association we conducted a systematic review and meta-analysis of cohort studies published on the subject. We searched the PubMed and Embase databases for studies of smoking and gallbladder disease up to January 9th 2015. Prospective studies were included if they reported relative risk estimates and 95 % confidence intervals of gallbladder disease associated with current, former or ever smoking and by number of cigarettes per day. Summary relative risks were estimated by use of a random effects model. We identified ten prospective studies including 59,530 gallbladder disease cases among 4,213,482 participants that could be included in the meta-analysis. The summary RR was 1.19 (95 % CI 1.12-1.28, I² = 46.9 %, n = 6) for current smokers, 1.10 (95 % CI 1.07-1.13, I² = 0 %, n = 6) for former smokers and 1.15 (95 % CI 1.13-1.18, I² = 0 %, n = 7) for ever smokers. In the dose-response analysis the summary relative risk was 1.11 (95 % CI 1.08-1.14, I² = 33 %, n = 3) per 10 cigarettes per day and although there was indication of nonlinearity there was a dose-dependent positive association with increasing number of cigarettes smoked per day. The current meta-analysis provides evidence of an increased risk of gallbladder disease associated with tobacco smoking.